The Dynamics of Real Interest Rates, Real Exchange Rates and the Balance of Payments in China : 1980-2002 - Jin, Zhongxia (IMF Working Papers; Working Paper ;, 2003)
Based on China's experience between 1980 and 2002, a cointegrated vector autoregression model was established to explore the relationships among real interest rates, real exchange rates and balance of payments in China. Taking into account institutional changes, the empirical study shows that significant and usually non-monotonic interactions exist between these three variables. The paper discusses theoretical and policy implications of the empirical result.